Peran Majelis Taklim Nurur Rahma sebagai Wadah Diskusi bagi Muslimah di Era Digital - Hendra Kurniawan; Intan Aprillia Silalahi; Amelia Putri; Dedi Rusdi Pohan; Pernando Aditya Jamil (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
This study aims to analyze the role of Majelis Taklim Nurur Rahma as a discussion forum for Muslim women in the digital era. Along with the rapid development of information technology, religious learning activities are required to adapt to digital platforms in order to remain relevant and accessible. This research uses a qualitative descriptive approach, with data collected through observations, interviews, and documentation involving administrators and members of Majelis Taklim Nurur Rahma. The results show that Majelis Taklim Nurur Rahma plays a significant role as a space for religious learning, sharing experiences, and strengthening social bonds among Muslim women. Digital media such as WhatsApp groups, social media, and online study sessions are utilized to support discussion activities, expand participation, and overcome limitations of time and place. However, challenges such as differences in digital literacy levels and limited access to technology are still encountered. Overall, Majelis Taklim Nurur Rahma demonstrates adaptability to digital developments while maintaining its core function as a religious and social discussion forum. This study concludes that the integration of digital media can enhance the effectiveness of majelis taklim activities if supported by adequate digital literacy and continuous guidance.